Skills for Success: Personal Development and Employability - Stella Cottrell (London Palgrave, 2015)
Each chapter encourages students to think reflectively about personal, academic and career goals and to plan a path to success. Rich in activities that develop valuable career skills, this revised and updated third edition has two new chapters on 'Taking charge of your life, learning and career' and 'What do employers really want?'.
Age Group: Adult
Keywords: Self Help; Personal Development; Nonfiction; (MGT102) Business Management Skills Development